Identidad de la provincia de El Oro, caso: cantón Marcabelí. - Rivera Bastidas, Carlos Samuel (2014)
The present investigation, Identity of the province of El Oro case Marcabelí Canton, Artistic project aimed at this corner, through a questionnaire and interviews, was intended to get a real diagnosis of the most relevant features in identity and culture.